e-MathJr Education for Kindergarten: a framework / Siti Nor Sophieana Mior ... [et al.] - Mior, Siti Nor Sophieana; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina; Mohamed Yusoff, Syarifah Adilah; Johan, Elly Johana; Rosmani, Arifah Fasha (Unit Penerbitan JSKM, 2024)
E-learning can be viewed as a natural development of remote learning, which has always benefited from the newest tools to appear in the environment of technologies for conducting education. Various subjects can be applied to e-learning which allow students to engage with educational materials in a playful and dynamic way. One of it is the mathematics subject. The area of mathematical development starting from early childhood is important to a child’s progress in primary and post-primary education. Kindergarteners will practice basic concepts of math, reading, writing, shapes, and so on. To replace the traditional learning methods in Mathematics, e-MathJr Education for Kindergarten was being developed. ADDIE Model is used in the system development. This mobile application will provide kindergarteners with an interesting and more engaging learning application through instant and personalized feedback.